Sources and Literature of Malaysian Law - Zakaria, Datin Shaikha (Journal of Malaysian and Comparative Law, 2019)
Malaysia is a federation of thirteen states consisting of the eleven states of Peninsular Malaysia, namely, Johore, Kedah, Kelantan, Negeri Sembilan, Pahang, Perak, Perlis, Selangor, Trengganu, Malacca and Penang, and two states in Borneo, namely, Sabah and Sarawak.